Adopting an Orphan Disease: Managing Sarcoidosis in the Era of Biologic Medications (Canadian Dermatology Today, 2020)
Sarcoidosis is a granulomatous immune-mediated inflammatory disorder. It remains a challenging disease to diagnose and treat because it has multiple cutaneous presentations, it can affect any organ system, and it is a diagnosis that can only be made when other granulomatous conditions, including infections, have been ruled out. However, making a diagnosis of sarcoidosis and providing effective treatment can be life-saving. An increased understanding of this complex condition has led to new treatment options, including the innovative off-label application of biologic medications and small-molecule inhibitors (SMIs). This article will review key clinical aspects of cutaneous sarcoidosis, provide a quick refresher on necessary investigations for the busy dermatologist, and review the evidence for use of biologic medications and SMIs in the treatment of cutaneous sarcoidosis.